Exploring Source Credibility when Communicating about Agricultural Science on Twitter - Allison R Fortner; Alexa J. Lamm; Abigail Borron; Jessica Holt; Allen J Moore (Journal of Applied Communications, 2022)
Universities must strategically communicate agricultural science to effectively reach millennials skeptical of agricultural innovations and constantly assessing the credibility of online information. Universities are trusted information sources and must maintain credibility on social media platforms such as Twitter, used by millennials to receive and share information. Source credibility seeks to understand message source and recipient characteristics that influence recipients’ perceptions of a source’s expertise and trustworthiness. The purpose of this study was to explore differences in engagement when specific factors affecting source credibility were emphasized when communicating with millennials about agricultural science on Twitter. The purpose was accomplished by describing the level of engagement and the differences in engagement observed between perceived gender, race, and age of university scientists. Over seven months, researchers wrote press releases about published journal articles authored by two or more diverse, university-affiliated scientists. They published multiple tweets about each release, with the only difference being the scientists’ headshots. Scientists were categorized as perceived male versus female, White versus Non-White, and older versus younger. Descriptive analysis of engagement metrics from 32 tweets found those with females performed better than those with males. Non-White scientist tweets performed better with the exception of engagement rate. Tweets featuring younger scientists received more engagement than older. The exploratory results implied tweets featuring young, Non-White females may elicit higher engagement. Future studies should examine if engagement metrics are correlated with source credibility dimensions. Strategically featuring diverse scientists in research communication may be utilized to build engagement in universities’ social media.
Keywords: source credibility; agricultural science communication; Twitter; university communication; millennials